Considerations on Gastronomic Tourism as a Component of Sustainable Local Development - Dan Mihnea Diaconescu; Remus Moraru; Gabriela Stănciulescu (Amfiteatru Economic)
Tourism is a multi-faced activity that links the economic, social and environmental components of sustainability. Firstly, this research analyses residents’ perceptions of the impact of tourism development and examines the factors that influence the support for sustainable tourism development. Secondly, the research discusses Community Based Tourism (CBT) and its positive impact of tourism development; CBT is connected to community’s capacity to protect itself from outside threats by negotiating the quality of tourism development. Thirdly, Gastronomic Tourism development is depicted as an interaction between outside developers and local residents that ultimately builds a sustainable dialogue for growth of tourism. Usually, the partnerships established between local community residents and outside tourism developers began with initial resistance from residents and led to the following sequence of behaviour: town meetings, formal organization of residents, petitioning, public demonstration, and legal action. By examining collective action narratives in the study communities, a framework for sustainable rural tourism development is built to understand relationships between tourism impacts, sustainable development and community identity. Findings indicate that residents see tourism as a development factor. The natural, economic, and social-cultural environment as well as infrastructure, age, gender and education are factors that influence the sustainable development of tourism and gastronomic tourism.